Improving Students’ Score in Writing Procedure Text by Using the Media “Writing Guidance Sheet“ at Islamic Senior High School - Ya Habibi (Research Journal on Teacher Professional Development, 2023)
AbstractThis study aims to improve students' procedural text writing skills using picture-based writing guidance sheet media in the English learning process. A classroom action research was conducted in two cycles at Nurul Aqsho Islamic Senior High School in Tanjung Jabung Timur. Data collection techniques involved observation, tests, and questionnaires. The results of the study show that the use of picture-based writing guidance sheet media significantly improves students' writing skills. This improvement is evident from the increase in the average scores of students from 51 in the preliminary study to 94.33 in the second cycle. Furthermore, students' responses to this media are also positive. These findings support the use of writing guidance sheet media as an effective tool in teaching procedural text writing in English.Keywords: Learning Media, Writing Guidance Sheet, Writing Skills, Procedure Text, Classroom Action Research, High School.